2020
DOI: 10.1620/tjem.250.243
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin for Predicting Intensive Care Unit Admission and Mortality in Patients with Pneumonia

Abstract: Pneumonia is one of the most common causes of hospital admissions and mortality, and it is responsible for significant socioeconomic burden worldwide. Neutrophil gelatinase-associated lipocalin (NGAL) is a 25-kDa protein, which is involved in iron trafficking and has chemostatic and bacteriostatic effects. NGAL is also known as an early marker of many inflammatory diseases. However, little is known about the role of NGAL in the management of pneumonia. Thus, this study aimed to investigate whether plasma NGAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…For example, LCN2 limits iron uptake in the host, which reduces bacterial growth during the innate immune response [10][11][12]. In experimental models of pneumonia or sepsis, LCN2 deficiency increases bacterial proliferation and lowers host survival [13][14][15][16][17]. In contrast, LCN2 deletion has been shown to markedly attenuate the production of proinflammatory cytokines in mice with ARDS [18].…”
Section: Ivyspringmentioning
confidence: 99%
“…For example, LCN2 limits iron uptake in the host, which reduces bacterial growth during the innate immune response [10][11][12]. In experimental models of pneumonia or sepsis, LCN2 deficiency increases bacterial proliferation and lowers host survival [13][14][15][16][17]. In contrast, LCN2 deletion has been shown to markedly attenuate the production of proinflammatory cytokines in mice with ARDS [18].…”
Section: Ivyspringmentioning
confidence: 99%
“…Pneumonia contracted from the community, gastroenteritis, and meningitis were the most frequently identi ed infections necessitating PICU hospitalization. [34] In the study of Min et al, 2020, 241 hospitalized patients with pneumonia, examined the relationship between plasma levels of NGAL, admission to the intensive care unit, and in-hospital death. Patients who were hospitalized to the ICU had NGAL levels that were noticeably greater than the ones who were discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this, patients who did not survive had a higher likelihood of having higher NGAL levels than those who did. [35][36][37] Previous reports for patients with bacterial meningitis, high levels of NGAL in their CSF were found. [38,39] Additionally, NGAL is a highly sensitive and reliable marker for differentiating bacterial meningitis from a variety of other CNS Page 6/16…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 exists as a monomer or heterodimer, which is produced by both neutrophils and epithelial cells, and in dimeric form that is exclusively released by neutrophils [ 4 , 29 ]. It has traditionally been used as a marker of acute kidney failure [ 30 ], but it has been also proposed as a biomarker of infection [ 12 ], including respiratory tract infections (RTI) [ 7 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that plasma LCN2 concentration is a valuable biological marker in the assessment of the severity and prediction of the prognosis of patients with CAP [ 7 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%